The effect of final irrigation on the penetrability of an epoxy resin-based sealer into dentinal tubules: a confocal microscopy study - Jardine, Alexander Pompermayer; Rosa, Ricardo Abreu da; Santini, Manuela Favarin; Wagner, Márcia; Só, Marcus Vinícius Reis; Kuga, Milton Carlos [UNESP]; Pereira, Jefferson Ricardo; Kopper, Patrícia Maria Poli (Springer Nature, 2015)
Introduction The aim of this study was to compare the effect of QMix, BioPure MTAD, 17 % EDTA, and saline on the penetrability of a resin-based sealer into dentinal tubules using a confocal laser scanning microscope (CLSM) and to describe the cleaning of root canal walls by SEM. Methods Eighty distobuccal roots from upper molars were selected and randomly divided into four groups (n=20) before root canal preparation according to the solution used in the final rinse protocol (FRP): QG (QMix), MG (BioPure MTAD), EG (17 % EDTA), and CG (control group: saline). Ten roots of each group were prepared for SEM, and images (×2000) from the canal walls were acquired. The remaining canals were filled with a single gutta-percha cone and AH Plus with 0.1 % Rhodamine B. The specimens were horizontally sectioned at 4 mm from the apex, and the slices were analyzed in CLSM (×10). Sealer penetration was analyzed with Adobe Photoshop software. Results QG and EG presented similar amounts of sealer penetration (P>.05). MG and CG presented the lowest penetrability values (P<.05). The best results for smear layer removal of the apical third of the root canal were achieved by the QG and EG groups when compared with MG and CG (P<.05). Conclusions Seventeen percent EDTA and QMix promoted sealer penetration superior to that achieved by BioPure MTAD and saline. Clinical relevance Despite studies have not confirmed the relationship between sealing ability of endodontic sealers and their penetration in dentinal tubules, sealer penetration assumes importance, since endodontic sealers, unlike guttapercha, are able to penetrate in dentinal tubules, isthmus, and accessory canals, filling the root canal system.
Keywords: Endodontics; Confocal laser scanning microscopy; Scanning electron microscopy; Smear layer; Root canal irrigant; Final irrigation solution; Irrigação endodôntica